Principal component analysis of clinical, mental health, and behavioral factors in a mixed population: insights for public health strategies - Utchimahali, Suguna; Kannan, S.; Velayutham, Kumaravel (International Journal Of Community Medicine And Public Health, 2024)
Background: Non-communicable diseases (NCDs) such as type 2 diabetes mellitus (T2DM) and mental health disorders set forth substantial public health challenges in Tamil Nadu, India. Formulating targeted therapies requires an understanding of the behavioural, mental health, and clinical variables. Aim was to explore patterns in health outcomes among a mixed population with and without T2DM, focusing on socio-demographic, clinical, and mental health factors using principal component analysis (PCA). Methods: A cross-sectional study was conducted during April 2020 to March 2021 with 614 participants (307 with T2DM and 307 without diabetes) in Alpha Hospital and Research Centre, a tertiary healthcare centre in Madurai, Tamil Nadu, India. Statistical analysis was done using IBM statistical package for the social sciences (SPSS) version 23. Results: PCA discovered nine components from a set of clinical, behavioural, and socio-demographic variables, with a KMO value of 0.915 and Bartlett’s Test of Sphericity showing significant Chi-square (11,932.50, p<0.001). 52.23% of the total variance was explained by the first five components. The clustering of stress, anxiety and depression in mental health components as well as the importance of glycaemic management and physical exercise as metabolic markers were among the key findings. Risky behaviours like smoking and alcohol consumption are exposed to have strong associations with adverse effects on health. Conclusions: This study highlights novel insights on the interactions between clinical, mental health and behavioural aspects among the population of Tamil Nadu. Public health strategies converging on stress reduction, mental health support and chronic disease management are recommended for improved health outcomes.